1992
DOI: 10.1002/etc.5620110401
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of EPA's rapid bioassessment benthic metrics: Metric redundancy and variability among reference stream sites

Abstract: The data analysis scheme used in the U.S. Environmental Protection Agency's (EPA's) rapid bioassessment protocols (RBPs) integrates several community, population, and functional parameters (or metrics) into a single assessment of biological condition. A reference data base of macroinvertebrate data obtained from 10 ecoregions in Oregon, Colorado, and Kentucky was used to evaluate the appropriateness and variability of the benthic metrics and the similarities of results among ecoregions. Several statistical pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(36 citation statements)
references
References 7 publications
0
36
0
Order By: Relevance
“…Such approaches define the normal structure of a system, measure deviations from normal and thereby evaluate severity of impairment. This method has been effective in freshwater habitats (Green and Vascotto, 1978;Lenat, 1988;Barbour et al, 1992;Rosenburg and Resh, 1993). Another approach widely used in wetland systems is the hydrogeomorphic (HGM) approach (Brinson, 1993;Smith et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Such approaches define the normal structure of a system, measure deviations from normal and thereby evaluate severity of impairment. This method has been effective in freshwater habitats (Green and Vascotto, 1978;Lenat, 1988;Barbour et al, 1992;Rosenburg and Resh, 1993). Another approach widely used in wetland systems is the hydrogeomorphic (HGM) approach (Brinson, 1993;Smith et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Benthic macroinvertebrate populations are notorious for background variation due to spatial and temporal heterogeneity [17,18]. Hannaford and Resh [16] demonstrated considerable variation due to human error in biological assessments, and others have shown that metric values varied significantly among replicates [20] and seasons [7]. Hannaford and Resh [16] demonstrated considerable variation due to human error in biological assessments, and others have shown that metric values varied significantly among replicates [20] and seasons [7].…”
Section: Introductionmentioning
confidence: 99%
“…Both annual temperature range and maximum temperature tend to increase downstream in most river systems (Minshall and Robinson, 1998) Hilsenhoff's (1987) .24, No.2, 1999 Downloaded by [198.91.36.79] at 07:46 06 October 2014 developed explicitly for the assessment of organic enrichment, although Barbour et al (1992) found it to be a good general indicator of stress on stream benthos.…”
Section: Resultsmentioning
confidence: 97%